Climate variability and its impact on sanitation facility choice in Ethiopia - Bahre Gebru; Katarina Elofsson; Franklin Amuakwa-Mensah; George Marbuah (Discover Water, 2025)
Abstract Climate change is expected to affect precipitation and temperature, with consequences for water availability and sanitation. The purpose of this paper is to investigate how precipitation and temperature affect households’ decisions on sanitation facilities that vary in their dependence on water for operation. To this end, we use household-level panel data from the Ethiopia Socioeconomic Survey in combination with location-matched, high-resolution weather data. Employing a panel fixed-effects regression model, the findings reveal that higher precipitation is significantly associated with an 18% lower (higher) likelihood of using improved (unimproved) sanitation facilities, respectively. Higher temperature has the opposite effect. Both precipitation and temperature have heterogeneous impacts: the effect of precipitation is significant only in male-headed households, while temperature affects the use of shared improved facilities in towns and urban areas. One potential explanation for the influence of precipitation is that heavy precipitation can disrupt access to piped water and sanitation networks by causing physical damage to infrastructure. Furthermore, higher temperature may accelerate the decomposition of solids in septic tanks, thereby reducing the need for water. These findings could help policymakers and practitioners implement evidence-based sanitation interventions to increase access to improved sanitation facilities.